GAMBARAN KUALITAS HIDUP PASIEN KANKER STADIUM LANJUT YANG MENJALANI RADIOTERAPI PALIATIF DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Harfendi, Gita Nadya; Yuliasti, Riri; ", Winarto (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTAdvanced stage cancer patients in need of palliative care for to achieve the maximum quality of life and palliate suffering. Quality of life consists the dimentions of physical, psychological, social relationships and environment. Palliative radiotherapy is one of the modalities to achieve a good quality of life. Radiotherapy ionization energy overcome the symptoms by direct and indirect action. The purpose of this study was to describe the quality of life of patients with advanced cancer lead the palliative radiotherapy at Arifin Achmad Hospital in Riau province. The method was descriptive study using medical records of patients who lead the palliative radiotherapy and interview using a questionnaire WHOQOL-BREF. We obtained 24 samples with characteristics : the largest age group of 36-45 years (33.3%), mostly females (79,9%). The most commonly primary malignancies diagnosis was breast cancer (75.0%) and mostly local irradiations was found in this study (79.2%). The highest mean of dimentions of quality of life was the environtment dimention (70,6%) and the lowest was the physical dimention (47,25%).Key words : Quality of life, palliative irradiation,WHOQOL-BREF, advanced stage cancer